Symbolism in traditional Malay boat crafting in the East Coast - Abdul Wahab, Mohd Rohaizat; Ramli, Zuliskandar; Ismail, Nurul Norain Akhemal; Abu Bakar, Nuratikah; Wan Azhar, Wan Nor Shamimi (Malaysian Institute of Planner, 2018)
The culture in the East Coast are rich in visual arts and performing arts inherited over time immemorial. The art is also found to have similarities in three different states, despite their geographical gap. The similarities are shared in dialects, languages, presentations, builds, and past legacy artefacts. The Malay craftsmanship is also dominated by the Malay community in the East Coast and it is also produced in the form of art and fashion. Artefacts such as boats, houses, and furniture are still visible until now and they have high artistic value. This research is aimed at displaying symbols produced by the Malay community on the craft of the boat. This art can be seen in the carvings and paintings produced on traditional Malay boats in the East Coast. This art does not only serve as an ornament and for its aesthetics, but also has its own symbolism. The decorative art produced shows that the three main aspects necessary in Malay art are function, aesthetics, and ethics. The belief in the existence of supernatural powers - which preserve and safeguard their safety at sea and their ability to get income from marine products - underpins the craft of this decoration art.